Antimicrobial and Cytotoxic Activity of Withania somnifera - Atta, Waham S; Al-Ani, Nabeel K (Al-Nahrain Journal of Science, 2018)
Withania somnifera (L) Dunal popularly known as ‘Ashwagandha’ had been used in folk medicine. Ten grams of leaves powder were used to extract the active substances as water, ethanol, and acetone extracts. The extracts were subjected to chemical analysis to identify the active components, Alkaloids, Glycosides, Saponins, Flavonoids, Fixed oil was present in ethanol, acetone and water extracts while terpene was absent in water extract, Proteins were not found in acetone extract, Tannins were absent in all types of extracts. HPLC analysis revealed that all types of Withania extracts contained two types of Alkaloids (Withanolide-A and Withaferin-A), seven types of Flavonoids (Naringenin, Catechin, Luteolin, Hesperetin, Kaempfero, Apigenin and Naringin) and two types of Saponins (Sitoindosides VII and Sitoindosides VIII) appeared as different peaks in same retention times with standard. Withania extracts contained numbers of active group detected by FTIR. Antimicrobial activities for all types of extracts werecarried out against different types of bacteria and fungi but only Acetone extract showed antimicrobial activity on the fungus (Trichophyton violaceum). W. somnifera extracts had cytotoxic effect on HepG2 cell line, higher cytotoxic effect in ethanol extract appeared at 120 mg/ml concentration, Water extract was inbetween and acetone extract was the lowest one.